2008
DOI: 10.1016/j.ab.2007.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a one bead–one compound combinatorial library for β-actin identifies molecules active toward Ramos B-lymphoma cells

Abstract: The search for small molecules that specifically recognize protein targets is a laborious process if conducted in a one protein-one compound manner. A high-throughput antibody-based screening of one bead-one compound (OBOC) combinatorial small molecule libraries is described here, whereby libraries containing thousands of different small molecule ligands are synthesized on individual TentaGel beads and simultaneously screened for protein binding to individual beads, each with a different compound. The use of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Linear or cyclic mimotopes from six irrelevant allergens ( Supplementary Table 3) were also mapped to Met e 1 using EpiSearch (Table 2, Figure 4d). Only half of the irrelevant inputs matched to Met e 1, and only a prediction based on Pru p 3 overlapped with a short epitope at Met e 1 [25][26][27][28][29][30] ; none overlapped with Pen a 1 epitopes.…”
Section: Comparison Between Predicted and Genuine Epitopesmentioning
confidence: 97%
See 1 more Smart Citation
“…Linear or cyclic mimotopes from six irrelevant allergens ( Supplementary Table 3) were also mapped to Met e 1 using EpiSearch (Table 2, Figure 4d). Only half of the irrelevant inputs matched to Met e 1, and only a prediction based on Pru p 3 overlapped with a short epitope at Met e 1 [25][26][27][28][29][30] ; none overlapped with Pen a 1 epitopes.…”
Section: Comparison Between Predicted and Genuine Epitopesmentioning
confidence: 97%
“…We adopted a modified two-stage subtraction screening approach 25 to screen OBOC libraries (Supplementary Figure 2). For each round of screening, 80 mL of the library (approximately 60 000 beads) was used and the incubation process was carried out in a polypropylene disposable column (Qiagen, Hilden, Germany).…”
Section: Two-stage Subtraction Screening Of Oboc Librariesmentioning
confidence: 99%
“…It has been demonstrated [23], in fact, that the content of a single bead (potentially carrying a single oligo-peptide structure) after contact with a crude protein extract, is constituted of a few proteins -some dominant and other minor species. In view of discovering specific peptide binders from a large library for the separation of one protein, it has been found that a single bead is capable of capturing more than a single species with presumably different dissociation constants [34,35]. As the interaction phenomenon is governed by the law of mass action, displacements effects are not only dependent on affinity constants but also on the relative concentration of species having affinity for the same peptide ligand.…”
Section: Binding and Release Mechanismsmentioning
confidence: 99%
“…This was the case of small ligands active against actin present in Ramos B-lymphoma cells (Miyamoto et al, 2008). The screening procedure was performed by two distinct steps.…”
Section: Examples Of Successful Affinity Peptide Ligands Discoverymentioning
confidence: 99%